Math Galaxy: Jelajah SPLDV dalam Kelas Terbalik untuk Meningkatkan Motivasi dan Hasil Belajar Matematika: Math Galaxy: Jelajah SPLDV in a Flipped Classroom to Enhance Mathematics Learning Motivation and Outcomes - Rezeki, Maulida (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Low motivation and learning outcomes often challenge mathematics learning, a problem in class VIII B of SMP Negeri 13 Palangka Raya. Initial observations revealed that 67% of students felt bored and only 33% achieved learning mastery on the System of Linear Equations in Two Variables (SPLDV) topic. This classroom action research aims to describe the improvement in motivation and mathematics learning outcomes of students on the topic of SPLDV using a flipped classroom model with the assistance of the Math Galaxy: Jelajah SPLDV media developed independently by the researcher. Data were collected through reflection questionnaires to measure motivation and essay tests to measure learning outcomes. The study's results demonstrated significant effectiveness, as evidenced by a decrease in student boredom to 0% and an increase in the learning mastery rate from 33% to 81%. These findings conclude that combining the Math Galaxy: Jelajah SPLDV media and the flipped classroom model effectively enhances students' motivation and learning outcomes. The uniqueness of this research lies in the creation of contextual and specific learning media, proving that teachers can be innovators in creating learning solutions relevant to the needs of their classes.